Does Color Matter on Web User Interface Design - Wirania Swasty; Andreas Rio Adriyanto (Bina Nusantara University, 2017)
Emotional advertising on the Internet such as websites and social media can be highly beneficial for Small Medium Enterprises (SMEs). However, not all ofSMEs have a website that meets all of the principles of website design which are persuasive. Moreover, the color is rarely considered in making websites to raise the emotional bonding between the products and audiences of SMEs. Literature review, observation to four websites as case studies, and questionnaires distributed to respondents randomly were performed. This research aimedto evaluate the extent to which SMEs from Bandung exploited the use of color as an element in the web User Interface (UI) design and to analyze whether thecolor could provide emotional bonding, so the visitors were interested in purchase or trial of the product. This research finds that participants responses to color are various in different demographic factors. Zananachips.com is considered to successfully utilize the color in the web UI design to build its brand identity, raise interest in the trial of the product, and engage the consumer with the website. This research is expected to be a reference forSMEs in creating emotion, motivation, and persuasion through website design.